(NOT THE) GOOD NEWS FOR TODAY. Issue 3 (July 2019) - Waters, Mark
Abstract : This article explores some current themes in radical theology in an attempt to find ways forward for progressive evangelism. First, the wide range of social, technological and cultural changes which have occurred over the last two centuries are considered, together with how they have contributed to the deconstruction of the credibility of much traditional doctrine and belief. Then themes of postmodernism, a/theism, a theology of the unconditional, and welcoming the death of God and the disappearance of the big Other are surveyed.